Speculative evaluations : essays on a pluralistic universe - McDonald, H. P. (Value Inquiry Book Series, 2012)
This book evaluates competing theories on speculative topics, such as nature, technology, space, time, and the relation of mind and matter. The general thesis is the actuality of principles in the form of laws, norms and other general principles in a plastic world, tying together the actualization of "oughts" and other principles. The result is a pluralistic universe, endorsing the pragmatic view of the world. The book examines nature, being, reality and other traditional issues in this light, critically evaluating many historical approaches.